LEVEL OF TRADERâS KNOWLEDGE WITH RHODAMIN B CONTAMINATION OF SHRIMP PASTE IN THE GEDONG KUNING MARKET YOGYAKARTA - Sunarti, Agni Yuwanna Bhakti & (Proceeding of International Congress, 2014)
Background. Food additive is a substance that is added to food to change the nature and shape of food.The use of food additives is set by food safety laws. However, the misuse of food additives often found inthe field. One cause of irregularities in the use of food additives is less knowledge of food additives. SomeResearch was discovered contamination dangerous food additives in various types of food products, likecrackers, snack foods,and instant seasoning. Based on observations made researchers found thecharacteristics of shrimp paste in the Gedong Kuning market Yogyakarta has a striking reddishâbrowncolor. Striking colors found in the paste is a screening to determine initial Rhodamine B contamination inshrimp paste. The purpose of this study to determine the relationship Level of traderâs Knowledge withRhodamine B contamination in shrimp paste in the Gedong Kuning market Yogyakarta.Methods. The research was in cross sectional study with 35 person traders of shrimp paste. Samplingtechnical with total population traders of shrimp paste in Gedong Kuning Market, yogyakarta. Level ofknowlegde was measured with kuesioner, and Rhodamin B measured with Thin Layer Chromatography(KLT).Result. The result showed 68.6 % shrimp paste contain Rhodamin B. Level of traderâs knowledge showed48.8% was not good knowledge. Statictic examination with chi square showed there is correation aboutlevel of traders knowledge with rhodamin B contamination in shrimp paste in Gedong Kuning marketYogyakarta.Conclution. There is correlation about level of traderâs knowledge with rhodamin B contamination inshrimp paste in Gedong Kuning Market Yogyakarta.Key words : Rhodamin B, chromatography, food addition